ANAESTHETIC EFFECTS OF MEDETOMIDINE HCl WITH PROPOFOL, KETAMINE AND CHLORAL HYDRATE IN EQUINES - H. Akbar; M. A. Khan; M. S. Khan; M. A. Khan; S. G. Bokhari; A. Nasir; A. A. Anjum (Journal of Animal and Plant Sciences, 2014)
Efficacy of medetomidine HCl anesthesia was evaluated in 48 horses, divided randomly into six groups (n=8). Initially, propofol, ketamine and chloral hydrate were evaluated individually as sole anesthetic drugs in groups A C and E, respectively. Later on the efficacy of medetomidine HCl as pre-anesthetic was assessed by using it in combination with other drugs. In group B, medetomidine HCl was used at 15µg/Kg BW and anesthesia was induced with propofol. Similarly, in group D, the combination of medetomidine HCl and ketamine was used, whereas in group F, medetomidine HCl was combined with chloral hydrate for production of anesthesia. The anesthesia thus produced in each animal was evaluated in order to find out the best anesthetic combination in horses. Statistical analysis of the parameters including induction, sedation, analgesia, recumbency and recovery was carried out at significance level of (P<0.05). Results of medetomidine used in combination with propofol, ketamine and chloral hydrate (groups B, D and F) were efficient than alone. Amongst the six groups, the most rapid induction (1.87±0.83) and sedation scores (1.87±0.83) were recorded with ketamine. Propofol manifested the lowest analgesia and recumbency scores of (1.50±0.53) and (1.87±0.64) with average time 10-20 minutes. The combination of medetomidine and chloral hydrate (group F) depicted the longest duration of sedation (4.75±0.70), recumbency (5.25±0.70), sedation (3.25±0.70), analgesia (4.75±0.70) and recovery (4.50±1.2).
Keywords: Anesthesia; Induction; Recumbancy; Sedation; Analgesia and Recovery